Global Experience With the Nellix Endosystem for Ruptured and Symptomatic Abdominal Aortic Aneurysms. (February 2016) - Reijnen, Michel M. P. J.; de Bruin, Jorg L.; Mathijssen, Elke G. E.; Zimmermann, Eric; Holden, Andrew; Hayes, Paul; Krievins, Dainis; Böckler, Dittmar; de Vries, Jean-Paul P. M.; Thompson, Matt M.
Purpose: To assess the feasibility and safety of the endovascular aneurysm sealing (EVAS) technique in the treatment of acute abdominal aortic aneurysm (AAA).Methods: A retrospective, multicenter, observational study was conducted at 8 centers (7 European and 1 in New Zealand) experienced with EVAS in the elective setting. From February 2013 to April 2015, 58 patients (mean age 74±9 years; 46 men) with an acute AAA were treated (28 ruptured and 30 symptomatic). The primary endpoint of the study was 30-day mortality; secondary endpoints included endoleak, reinterventions, and 30-day morbidity.Results: The overall intensive care unit and hospital stays were 2.2±6.6 days and 9.7±11.4 days, respectively. Thirty-day mortality rates were 32% (9/28) for the ruptured group and 7% (2/30) for the symptomatic group, with morbidity rates of 57% and 17%, respectively. Early endoleak was present in only 2 (3%) patients, one in each group; both leaks were type Ia. Reinterventions within 30 days were performed in 8 patients in the ruptured group; in the symptomatic patients, the only perioperative reintervention was embolization a type Ia endoleak. The mean follow-up was 9.3±3.1 months in the ruptured group and 12.4±5.4 months in the symptomatic group. The mean aneurysm diameter at 30-day follow-up was 71.8±16.0 mm compared with 74.7±15.7 mm preoperatively in the ruptured group and 66.1±13.5 mm compared with 65.8±13.0 mm in the symptomatic group.Conclusion: EVAS in the acute setting appears safe and feasible and concordant with the literature for endovascular aneurysm repair. More robust prospective and comparative data are required to establish the position of the technique in the treatment algorithm of acute AAA.